Status of coral reefs of Upolu (Independent State of Samoa) in the South West Pacific and recommendations to promote resilience and recovery of coastal ecosystems. Issue 1 (April 2018) - Ziegler, Maren; Quéré, Gaëlle; Ghiglione, Jean-François; Iwankow, Guillaume; Barbe, Valérie; Boissin, Emilie; Wincker, Patrick; Planes, Serge; Voolstra, Christian R.
Abstract: Coral reef ecosystems worldwide are immediately threatened by the impacts of climate change. Here we report on the condition of coral reefs over 83 km of coastline at the island of Upolu, Samoa in the remote South West Pacific in 2016 during the Tara Pacific Expedition. Despite the distance to large urban centers, coral cover was extremely low (<1%) at approximately half of the sites and below 10% at 78% of sites. Two reef fish species, Acanthurus triostegus and Zanclus cornutus, were 10% smaller at Upolu than at neighboring islands. Importantly, coral cover was higher within marine protected areas, indicating that local management action remains a useful tool to support the resilience of local reef ecosystems to anthropogenic impacts. This study may be interpreted as cautionary sign for reef ecosystem health in remote locations on this planet, reinforcing the need to immediately reduce anthropogenic impacts on a global scale. Highlights: We assessed the health of reef ecosystems at Samoa in the remote South West Pacific. Despite the distance to large urban centers, live coral cover was extremely low. Reef fish were 10% smaller than at neighboring islands. Coral cover was higher within two local marine protected areas. Remote reef ecosystems are not immune to local and global anthropogenic impacts.